Outcome of Targeted Driving Pressure Mechanical Ventilation in ARDS patients (Bangladesh Critical Care Journal, 2024)
Background: Lung protective strategy in acute respiratory distress syndrome (ARDS) patients is based on low tidal volume (VT), lower end-inspiratory (plateau) pressure and higher positive end-expiratory pressure (PEEP). But to predict body weight adjusted tidal volume, heterogeneous pathology of the lung in ARDS with different respiratory system compliance (CRS) is not considered. In driving pressure (ΔP=VT / CRS) tidal volume (VT) is normalized to functional lung size. It is unclear whether mechanical ventilation targeting driving pressure (ΔP) is more effective than low tidal volume ventilation (LTVV) in patients with ARDS.Materials and Methods: An open labelled randomized controlled trial was conducted at Intensive Care Unit of Dhaka Medical College Hospital, a tertiary care referral hospital over 12 months from March 2021 to February 2022. Ninety two patients with ARDS, defined by the Berlin criteria, requiring mechanical ventilation were randomized to 1:1 ratio after enrollment in the study using simple random sampling, one group receiving targeted driving pressure (ΔP) that is 0.05), except for the duration of mechanical ventilation (MV), which was significantly shorter in the Targeted ΔP group (p